2003
DOI: 10.1152/ajpgi.00214.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin-1 attenuates TNF-induced epithelial barrier dysfunction: role of novel PKC isozymes

Abstract: Tumor necrosis factor (TNF) increases epithelial permeability in many model systems. Protein kinase C (PKC) isozymes regulate epithelial barrier function and alter ligand-receptor interactions. We sought to define the impact of PKC on TNF-induced barrier dysfunction in T84 intestinal epithelia. TNF induced a dose- and time-dependent fall in transepithelial electrical resistance (TER) and an increase in [(3)H]mannitol flux. The TNF-induced fall in TER was not PKC mediated but was prevented by pretreatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…Therefore, due to maintenance of PKCδ activation, bryostatin-1 could be translated into therapies for other disorders benefiting from consistent PKCδ activation. Bryostatin-1 has been shown in one study to enhance solute barrier and prevent the loss of barrier caused by TNF-α in T84 intestinal epithelia, and in another to have no affect on T84 epithelial barrier integrity [59,60]. The fact that studies show bryostatin-1 does not decrease epithelial barrier function and we show no change in endothelial barrier with bryostatin-1 treatment is important.…”
Section: Discussionsupporting
confidence: 40%
“…Therefore, due to maintenance of PKCδ activation, bryostatin-1 could be translated into therapies for other disorders benefiting from consistent PKCδ activation. Bryostatin-1 has been shown in one study to enhance solute barrier and prevent the loss of barrier caused by TNF-α in T84 intestinal epithelia, and in another to have no affect on T84 epithelial barrier integrity [59,60]. The fact that studies show bryostatin-1 does not decrease epithelial barrier function and we show no change in endothelial barrier with bryostatin-1 treatment is important.…”
Section: Discussionsupporting
confidence: 40%
“…In a similar fashion, L32 and GAPDH expression remained constant indicating equal loading. Bryostatin stimulates various PKC isoforms in certain cell lines (46,47). Treatment with bryostatin induced cIAP-2 mRNA expression and this induction was completely blocked by GF109203x treatment (Fig.…”
Section: Ciap-2 Regulation In Human Colon Cancersmentioning
confidence: 87%
“…It is thus not surprising that the effects of PKC signaling in cells are highly complex and seem to vary widely with respect to experimental conditions as well as tissue and cell types. For example, pharmacological studies suggest that PKC-⑀, a member of novel PKC subfamily, mediates cytokine-induced disruption of the intestinal cells (Yoo et al, 2003b). We previously showed that attenuation of the novel PKC isoform, PKC-␦, via molecular interventions protects against oxidantinduced damage to intestinal cells (Banan et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%